The Law of Eminent Domain and Forced Displacement in India - Patgiri, Dristirupa (Christ University Law Journal, 2024)
India, in the new millennium, found its place in the ranks of rapidly developing countries. The primary model of development has long been the ‘Western’ one, where the emphasis is on projects including the construction of factories, dams, mining, weapon-testing grounds and the like. These projects require large areas of land, which India began acquiring under the umbrella of the Land Acquisition Act of 1894. As land is finite, an increase in the number of such development projects led to large-scale forced evictions of vulnerable populations, with the law relying on the principle of ‘eminent domain’. This principle gives the right to the central and state governments to take away private property for ‘public purposes’. The Right to Fair Compensation and Transparency in Land Acquisition, Rehabilitation and Resettlement Act of 2013 repealed the Act of 1894 and ushered in a new era of hope for instances of development-induced displacement. However, the central government diluted this legislation by exempting certain categories of projects from the consent and social impact assessment (SIA) requirement. In the absence of specific international and national protective mechanisms, the human rights of development-induced displaced persons have suffered for generations.